2011
DOI: 10.1002/ajp.20937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proximity and activity on visual and auditory monitoring in wild Japanese Macaques

Abstract: Group-living primates monitor group members to maintain the spatial cohesiveness of the group. We examined the possibility that visual scanning (turning the head for more than 3 sec) and contact calls (coo calls) function as visual and auditory monitoring behaviors to avoid separation from group members in wild Japanese macaques. The rate of visual scanning increased as proximity to group members decreased and as mobile activities (foraging and moving) increased, compared with immobile activities (resting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Robinson (1981) found that wedge-capped capuchins (Cebus olivaceus) increased vigilance with increasing distance to nearest neighbor; conversely, Suzuki and Sugiura (2011) reported vigilance increased as distance to nearest group member decreased in Japanese macaque (Macaca fuscata) adult females. Baldellou & Henzi (1992), Busia et al (2016), de Ruiter (1986, Fragaszy (1990), Gould et al (1997), Isbell & Young (1993), Rose & Fedigan (1995), Steenbeek et al (1999), Stojan-Dolar & Heymann (2010) a , Treves (1998Treves ( , 1999c, van Schaik & van Noordwijk (1989), Watson et al (2015) No difference between sexes Cowlishaw (1998), Gould (1996), Gould et al (1997), Macintosh & Sicotte (2009), Smith, Kelez & Buchanan-Smith (2004, Teichroeb & Sicotte (2012), Treves (1998) Dominance Subordinates more vigilant than dominants Alberts (1994) b , Caine & Marra (1988), Gaynor & Cords (2012), Haude et al (1976), Keverne et al (1978), Pannozzo et al (2007) High-ranking individuals more vigilant Alberts (1994) c , Gould (1996), Gould et al (1997), Isbell & Young (1993), Rose & Fedigan (1995), Watson et al (2015) No effect of rank Robinson (1981) Adult females with Infants…”
Section: A R Ia Ti On I N P Ri M a Te V I Gi La N Ce S T U Di E Smentioning
confidence: 99%
See 4 more Smart Citations
“…Robinson (1981) found that wedge-capped capuchins (Cebus olivaceus) increased vigilance with increasing distance to nearest neighbor; conversely, Suzuki and Sugiura (2011) reported vigilance increased as distance to nearest group member decreased in Japanese macaque (Macaca fuscata) adult females. Baldellou & Henzi (1992), Busia et al (2016), de Ruiter (1986, Fragaszy (1990), Gould et al (1997), Isbell & Young (1993), Rose & Fedigan (1995), Steenbeek et al (1999), Stojan-Dolar & Heymann (2010) a , Treves (1998Treves ( , 1999c, van Schaik & van Noordwijk (1989), Watson et al (2015) No difference between sexes Cowlishaw (1998), Gould (1996), Gould et al (1997), Macintosh & Sicotte (2009), Smith, Kelez & Buchanan-Smith (2004, Teichroeb & Sicotte (2012), Treves (1998) Dominance Subordinates more vigilant than dominants Alberts (1994) b , Caine & Marra (1988), Gaynor & Cords (2012), Haude et al (1976), Keverne et al (1978), Pannozzo et al (2007) High-ranking individuals more vigilant Alberts (1994) c , Gould (1996), Gould et al (1997), Isbell & Young (1993), Rose & Fedigan (1995), Watson et al (2015) No effect of rank Robinson (1981) Adult females with Infants…”
Section: A R Ia Ti On I N P Ri M a Te V I Gi La N Ce S T U Di E Smentioning
confidence: 99%
“…Terms such as "gaze", Numerous studies appear to try and tackle this problem by using postural changes or eye movement in elements of their vigilance definitions ( Table 2). Some of these definitions take a very concise multifunctional form such as "head up, eyes open" (Cowlishaw, 1998) or "movement of the head and/or eyes" (Gaynor & Cords, 2012), whilst other authors have added postural requirements to vigilance definitions such as "lifting of the head" (Caine & Marra, 1988) or "turning the head" (Suzuki & Sugiura, 2011). Some are more precise such as "Raising and lowering of the line of vision by at least 30 degrees relative to the horizontal plane" (Bshary & Noe, 1997), or "Head movement of at least 458, in any direction" (Steenbeek et al, 1999).…”
Section: Primate Vigilance Definitionsmentioning
confidence: 99%
See 3 more Smart Citations